Long-term toxicity and efficacy of FLASH radiotherapy in dogs with superficial malignant tumors - Gjaldbæk, BW; Arendt, ML; Konradsson, E; Bastholm Jensen, K; Bäck, SÅ; Munck af Rosenschöld, P; Ceberg, C; Petersson, K; Børresen, B (Frontiers Media, 2024)
Introduction: FLASH radiotherapy (RT) has emerged as a promising modality, demonstrating both a normal tissue sparing effect and anticancer efficacy. We have previously reported on the safety and efficacy of single fraction FLASH RT in the treatment of oral tumors in canine cancer patients, showing tumor response but also a risk of radiation-induced severe late adverse effects (osteoradionecrosis) for doses ≥35 Gy. Accordingly, the objective in this study was to investigate if single fraction high dose FLASH RT is safe for treating non-oral tumors. Methods: Privately-owned dogs with superficial tumors or microscopic residual disease were included. Treatment was generally delivered as a single fraction of 15-35 Gy 10 MeV electron FLASH RT, although two dogs were re-irradiated at a later timepoint. Follow-up visits were conducted up to 12 months post-treatment to evaluate treatment efficiency and adverse effects. Results: Fourteen dogs with 16 tumors were included, of which nine tumors were treated for gross disease whilst seven tumors were treated post-surgery for microscopic residual disease. Four treatment sites treated with 35 Gy had ulceration post irradiation, which was graded as severe adverse effect. Only mild adverse effects were observed for the remaining treatment sites. None of the patients with microscopic disease experienced recurrence (0/7), and all patients with macroscopic disease showed either a complete (5/9) or a partial response (4/9). Five dogs were euthanized due to clinical disease progression. Discussion: Our study demonstrates that single fraction high dose FLASH RT is generally safe, with few severe adverse effects, particularly in areas less susceptible to radiation-induced damage. In addition, our study indicates that FLASH has anti-tumor efficacy in a clinical setting. No osteoradionecrosis was observed in this study, although other types of high-grade adverse effects including ulcer-formations were observed for the highest delivered dose (35 Gy). Overall, we conclude that osteoradionecrosis following single fraction, high dose FLASH does not appear to be a general problem for non-oral tumor locations. Also, as has been shown previously for oral tumors, 30 Gy appeared to be the maximum safe dose to deliver with single fraction FLASH RT.